THE ANGUISH AND FICTION CONTEMPORARY: AN AFTERTHOUGHT - Jacob dos Santos Biziak (Travessias, 2013)
Our aim in this article is to accomplish an afterthought concerning contemporary fiction. Taken as initial the afterthought of the role of the novel as fiction and its linking with the afterthought of mimesis in modernity, we aim to consider the presence of agony not only as a theme but also as a structural element of narratives. Eventually, we will make brief tallies of theses aspects in the work of Jos Saramago.